2009
DOI: 10.1177/0961203309106829
|View full text |Cite
|
Sign up to set email alerts
|

Limbic encephalitis associated with systemic lupus erythematosus

Abstract: A 34-year-old woman with systemic lupus erythematosus (SLE) presented with general fatigue, seizures and memory loss. Magnetic resonance imaging of the brain showed a high signal area in the mesial temporal lobe bilaterally. Computed tomography scan of the chest and abdomen and ultrasound of pelvis detected no malignancy and tumour marker, antibodies to antineuronal antibodies (anti-Hu, anti-Ta and anti-Ma) and antibodies to voltage-gated potassium channels were all negative. The present case is limbic encepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The classical manifestation of LE includes episodic memory impairment 9 , seizures 10 , confusion 16 , sleeping problems 18 , and psychiatric symptoms. 19 The most characteristic clinical feature is short-term memory loss, but associated symptoms such as confusion and seizures might limit the memory assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical manifestation of LE includes episodic memory impairment 9 , seizures 10 , confusion 16 , sleeping problems 18 , and psychiatric symptoms. 19 The most characteristic clinical feature is short-term memory loss, but associated symptoms such as confusion and seizures might limit the memory assessment.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that a convergence point between the three conditions involves an autoimmunity component shared by all of them. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case malignancy, tumour markers and the antineural antibodies were negative. The author concluded that shared autoimmunity may cause both limbic encephalitis and SLE 11. Tumefactive demyelination is one subtype of pathological spectrum of central nervous system inflammatory demyelinating diseases.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, there is one report where authors reported coexistence of common variable immunodefi-ciency and limbic encephalitis in a 16-year old female patient. 15 Other authors reported limbic encephalitis related to lupus erythematosus, 16,17 while there is a report of Vogt-Koyanagi-Harada disease associated with non-herpetic acute limbic encephalitis, 18 suggesting a possible link between autoimmunity disorders and LE.…”
Section: Discussionmentioning
confidence: 99%